Reinterpretation of the Story of Lea and Rahel and Its Contribution to Christian Education - Anita Inggrith Tuela; Esther Heydemans; Semuel Selanno (Peneliti.net, 2021)
The aim of this study was to describe and to analyze a Biblical text, the story of Leah and. In order to find and to answer the statement of the qualitative research methods was used. For the text analysis, the researcher used investigative feminist hermeneutic approach. In collecting data the techniques of: observation, interviews, and documentation studies were applied. In analyzing data, the techniques performed were reducing data, displaying data and verifying data. Data validation was carried out by credybility checking through triangulation, peer discussion and member checking and then transferability checking, dependability and confirmability checking. The study revealed that: Based on the reinterpretation with hermeneutic feminist investigation of the biblical text, the story of Leah and Rachel, women were abused by the unfair patriarchal culture. It was concluded that the reinterpretation of the biblical text from women perspective was requaried for the freedom and transformation, so that it could be contribution for transformative christian education.